Trees of the world : an illustrated identifier and encyclopedia - Russell, Tony, 1957-; Cutler, Catherine (Hermes House, 2012)
PLANT LIFE: GENERAL. This title features clear, accessible, informative text from the subject's leading experts, with 800 artworks and photographs. It features stunning visual profiles of each tree that illustrate details of bark, branches, shoots, leaves, needles, buds, flowers, cones, nuts and fruits, as well as changes through the seasons. It includes over 600 examples, from beech, oak, larch, lime and hornbeam to exotic fruit trees such as mango and breadfruit. This wonderful encyclopedia explains what a tree is, how it lives, grows and dies, and how its constituent parts - the buds, branches, flowers, leaves, roots, cones, fruit and bark - all play their role in its life-cycle. An identifier section covers trees of the tropics and trees of the temperate world, and includes over 600 examples, from lofty conifers and stately deciduous broadleaf trees to elegant palms and exotic flowering trees.